Effect of Glomus intraradices and Rhizobium on the Growth of Groundnut (Arachis hypogaea L.). - M. Lenin*, K. Ramakrishnan and (Journal of Ecobiotechnology, 2010)
Abstract Arbuscular mycorrhizal (AM) fungi can increase the capability of the root systems to absorb and translocate phosphorus (P) and minor elements through an extensive network of mycelium. AM fungi are commonly associated with legumes and can increase nutrient uptake of plants growing in high phosphate fixing soils. The present study the efforts of AM fungi Glomus intraradices and Rhizobium on groundnut Arachis hypogaea L. The AM fungi Glomus intraradices and Rhizobium inoculation plants resulted in production of highest biomass such as plant, shoot length, root length, number of leaves, total number of root nodules, fresh and dry weight of plants and the biochemical content such as chlorophyll ‘a’ and ‘b’, total sugar, starch content, proline, carbohydrates and protein contents. The inoculation of Glomus intraradices + Rhizobium showed an enhanced biomass when compared to other treatments. Department of Botany, Annamalai University, Annamalai Nagar – 608 002 Please Cite This Article As: K. Ramakrishnan and M. Lenin. 2010. Effect of Glomus intraradices and Rhizobium on the Growth of Groundnut (Arachis hypogaea L.). J. Ecobiotechnol. 2(5):01-08.